Cotton Textile Surface Investigation Before and After Deposition of the ZnO Coating by Sol-gel Method - S. Vihodceva; S. Kukle (Журнал нано- та електронної фізики)
In the present research the commercial type of cotton textiles were modified by the sol-gel method to evaluate sol-gel technology suitability for cotton textiles. The nanosol was deposited on the cotton textile by dipping process; as well evaluation of the dipping process for thin zinc oxide coating deposition was made. The analysis of the coated textile surface was carried out by Scanning Electron Microscope (SEM), Atomic Force Microscope (AFM) and energy dispersive X-ray (EDX) spectroscopy. Data received by SEM and EDX analyses evince that the deposited coatings are evenly distributed, not only on surface of yarns but in the depth of textile material as well and are resistant to the exploitation impact (laundry test). AFM analyse evince that the deposited zinc oxide coating constituted by spherical or ellipsoidal particles with 30-nm average diameter, assembled in larger clusters.